COVID-19 and mental health: challenges for the work of Social Workers - Costa, Giselle Mara Cardoso da; Moljo, Carina Berta (Argumentum, 2023)
This article reflects on the challenges posed to the work of social workers within the multidisciplinary team at the Centre for Psychosocial Care - Alcohol and Other Drugs (CAPS) in the municipality of Juiz de Fora - Minas Gerais within the context of the COVID-19 pandemic. It was based on the work experience of one of the authors in 2020, reflected upon in the light of a literature review. Configured as a report of the experience, it addresses aspects related to Public Health and Mental Health Policy, contextualizing them to the situation of public calamity. It demonstrates how the challenging context prompted positive changes in fulfilling the role of a CAPS in psychosocial rehabilitation through the collective effort of the team, mobilised to guarantee care under exceptional circumstances.